Skylux : using light to improve health and wellbeing : [an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand] - Gabel, Lisa (Massey University, 2013)
My project aims to explore the conflicting demands between the increasingly indoor- based urban lifestyle and our innate biological connection to nature, with a focus on using light to support physical and mental wellbeing. By intertwining the fields of industrial design, health, and science, the project aims to enhance workplace lighting beyond the scope of visual performance to support our internal biological rhythms. The project seeks to address our biological need for brighter, dynamically changing light by utilizing a variety of qualitative and quantitative research methods, including a collaborative design group and an ongoing connection with circadian scientists 1. Alongside providing light that supports our biological needs, the final design aims to reconnect indoor workers with the subtle qualities and cycles of nature, whilst raising awareness around the impact of light on our health and wellbeing through experiential discovery. By applying scientific knowledge through design, my project aims to improve public health and life quality, whilst also promoting a greater social shift towards enhancing our lifestyles with better awareness around the vital role of natural light for our health and wellbeing. The following project is a s mall step towards addressing a much larger issue that I believe is at the forefront of future lighting design. My project aims to explore the conflicting demands between the increasingly indoor- based urban lifestyle and our innate biological connection to nature, with a focus on using light to support physical and mental wellbeing. By intertwining the fields of industrial design, health, and science, the project aims to enhance workplace lighting beyond the scope of visual performance to support our internal biological rhythms. The project seeks to address our biological need for brighter, dynamically changing light by utilizing a variety of qualitative and quantitative research methods, including a collaborative design group and an ongoing connection with circadian scientists 1. Alongside providing light that supports our biological needs, the final design aims to reconnect indoor workers with the subtle qualities and cycles of nature, whilst raising awareness around the impact of light on our health and wellbeing through experiential discovery. By applying scientific knowledge through design, my project aims to improve public health and life quality, whilst also promoting a greater social shift towards enhancing our lifestyles with better awareness around the vital role of natural light for our health and wellbeing. The following project is a s mall step towards addressing a much larger issue that I believe is at the forefront of future lighting design. My project aims to explore the conflicting demands between the increasingly indoor- based urban lifestyle and our innate biological connection to nature, with a focus on using light to support physical and mental wellbeing. By intertwining the fields of industrial design, health, and science, the project aims to enhance workplace lighting beyond the scope of visual performance to support our internal biological rhythms. The project seeks to address our biological need for brighter, dynamically changing light by utilizing a variety of qualitative and quantitative research methods, including a collaborative design group and an ongoing connection with circadian scientists 1. Alongside providing light that supports our biological needs, the final design aims to reconnect indoor workers with the subtle qualities and cycles of nature, whilst raising awareness around the impact of light on our health and wellbeing through experiential discovery. By applying scientific knowledge through design, my project aims to improve public health and life quality, whilst also promoting a greater social shift towards enhancing our lifestyles with better awareness around the vital role of natural light for our health and wellbeing. The following project is a s mall step towards addressing a much larger issue that I believe is at the forefront of future lighting design.
Keywords: Phototherapy; Light therapy; Equipment; Design